PENGARUH EFEKTIVITAS PROGRAM KARTU TANI TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA BULO KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Sri Rahmayanti; Sapri; Muhammad Ikbal (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) IAIN Palu, 2023)
The farmer card is a card specifically designed to allocate subsidized fertilizers to farmers. This study aims to determine the level of community welfare towards the farmer card program in Bolu Village, Panca Rinjang District, Sidenreng Rappang Regency. The benefit of this research is that it can provide input, and information, and become material for policymakers related to organizational culture in the performance of village apparatus so that they can optimize good relations and become a consideration for further strategic steps. This research uses quantitative methods, the population in this study is the people of Bulo Village, Panca Rijang District, Sidenreng Rappang Regency who are registered as recipients of the Farmer Card Program as many as 600 farmers who are members of 28 farmer groups. Data analysis will be carried out using the SPSS program. The research data were analyzed using statistical tools consisting of measurement scale instruments, data quality tests, simple linear regression, ion and hypothesis testing. Hypothesis Ha: The effectiveness of the program has a significant effect on the welfare of the community in Bulo Village, Panca Rijang Distriand ct, Sidenreng Rappang Regency. Tcotable blof value or 10.087 1.66320 then Ha is accepted, meaning it is significant. So, Effectiveness influences/significantly affects Community Welfare in Bulo Village, Panca Rijang District, Sidenreng Rappang Regency. The percentage value of the indicator for the level of community welfare for the Farmer Program in Bulo Village, Panca Rijang District, Sidenreng Rappang Regency is 58% which is in the unfavorable category.